2008
DOI: 10.1038/nsmb.1429
|View full text |Cite
|
Sign up to set email alerts
|

Long single α-helical tail domains bridge the gap between structure and function of myosin VI

Abstract: Myosin VI has challenged the lever arm hypothesis of myosin movement because of its ability to take ~36-nm steps along actin with a canonical lever arm that seems to be too short to allow such large steps. Here we demonstrate that the large step of dimeric myosin VI is primarily made possible by a medial tail in each monomer that forms a rare single α-helix of ~10 nm, which is anchored to the calmodulin-bound IQ domain by a globular proximal tail. With the medial tail contributing to the ~36-nm step, rather th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
182
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(205 citation statements)
references
References 54 publications
(84 reference statements)
20
182
1
2
Order By: Relevance
“…In order to account for the observed beta angles of the CaMcontaining lever arms, we indicate a second point of dimerization immediately following the lever arm extension (red), as we have recently demonstrated (7). recently proposed by Spink et al (25). In this model, the CaMcontaining lever arm of myosin VI is extended by long single alpha helices and dimerization between the myosin VI monomers occurs only in the region of their cargo binding domains (approximately the position of the GCN4 leucine zipper in our HMM construct).…”
Section: Resultsmentioning
confidence: 99%
“…In order to account for the observed beta angles of the CaMcontaining lever arms, we indicate a second point of dimerization immediately following the lever arm extension (red), as we have recently demonstrated (7). recently proposed by Spink et al (25). In this model, the CaMcontaining lever arm of myosin VI is extended by long single alpha helices and dimerization between the myosin VI monomers occurs only in the region of their cargo binding domains (approximately the position of the GCN4 leucine zipper in our HMM construct).…”
Section: Resultsmentioning
confidence: 99%
“…Their logic was that a construct containing 835-1,035 did not dimerize and that the region of myosin VI that was originally thought to form a coiled coil has been proposed to be a stable single ␣-helix (SAH) (18,23,24). Thus, Spink et al (18) postulated that the SAH domain forms an extension of the short myosin VI lever arm, enabling the dimer to take large steps on actin. However, we subsequently demonstrated that a lever arm extension is formed upon dimerization by unfolding of a three-helix bundle (6), formerly known as the proximal tail (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Spink et al (18) concluded that dimerization of the full-length molecule involves only dimerization of the cargo-binding domains. However the construct that dimerized in their study contained residues 835-1,285, and the cargo-binding domain is from Ϸ1,035 to 1,285 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations